Performance Improvement of Generalized Energy Detection For Cognitive Radio - P.Venkatapathi; Khan, Habbulla; Rao , S.Srinivasa (International Journal of Psychosocial Rehabilitation, 2020)
An efficient spectrum utilization has been an important topic of interest because of the improved usage of wireless communications in governmental, commercial and personal capacities.Cognitive Radio (CR) is a potential solution to this inefficiency problem. The spectrum sensing issignificant function of CR. It is used to detect primary user. Energy Detection(ED) is a most commonly used technique for spectrum sensing.